2018
DOI: 10.3390/su10082740
|View full text |Cite
|
Sign up to set email alerts
|

Formulating and Optimizing a Novel Biochar-Based Fertilizer for Simultaneous Slow-Release of Nitrogen and Immobilization of Cadmium

Abstract: This study aimed to develop and optimize a novel biochar-based fertilizer composed of rice husk biochar and urea–hydrogen peroxide (UHP), which can simultaneously slowly release nitrogen and immobilize cadmium (Cd). Response surface methodology (RSM) was adopted to optimize the fertilizer formulation with the lowest nitrogen release rate. Under the optimized conditions, the cumulative nitrogen release rate of the biochar-based fertilizer was 17.63%, which was significantly lower than that of ordinary fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Interestingly, the application of biochar in agriculture can be an effective way to enhance soil fertility, as it may contain multiple minerals that are required for soil enrichment. Chen et al [21] reported the addition of biochar produced from cow dung to agricultural soil, and confirmed that P-laden biochar not only increased the germination rate, but also promoted plant growth. However, to the best of our knowledge, only limited information is available on the utilization of phosphorus from biochar produced from food waste-derived biomass.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, the application of biochar in agriculture can be an effective way to enhance soil fertility, as it may contain multiple minerals that are required for soil enrichment. Chen et al [21] reported the addition of biochar produced from cow dung to agricultural soil, and confirmed that P-laden biochar not only increased the germination rate, but also promoted plant growth. However, to the best of our knowledge, only limited information is available on the utilization of phosphorus from biochar produced from food waste-derived biomass.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the p-value of lack of fit (0.0709) in this model implies that the lack of fit was not significant. The insignificance of lack of fit indicated that the proposed model fit the experimental data and the independent variables or parameters have considerable effects on the response [19]. To summarize, the R 2 and the insignificant lack of fit have proven the reliability of the model.…”
Section: Model Adequacy Checkingmentioning
confidence: 89%
“…This approach overcomes the limitation of the traditional one-factor-at-a-time-method, where the interaction between the factors is hard to identify [17,18]. In this experiment, the Box-Behnken design (BBD), as the standard design of RSM [19], was adopted to statistically optimize the influencing factors and evaluate the effect of the influencing factors on the turbidity reduction in drinking water treatment. The dosage of FeCl 3 , dosage of SSG, and the settling time were chosen as the influencing factors.…”
Section: Design Of Experiments For Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature [12,[19][20][21][22][23][24], the content of toxic ions can be reduced in two ways: by removing them from waste or by reducing their mobility in the environment-immobilization.…”
Section: Introductionmentioning
confidence: 99%